Struggling for stability: international support for peace and democracy in post-civil war Nepal - Jörn Grävingholt; Karina Mroß; Lennart Bendfeldt; Yvonne Blos; Charlotte Fiedler; Karina Mroß (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
How can countries emerging from a conflict be supported on their path towards peace and democracy? Although this question has been the focus of recent attention, it remains unclear exactly what factors are critical to the success of external engagement in fragile states. To this end, this study aims to learn from the relatively successful case of Nepal.
Keywords: 330; Demokratie und Autokratie; Democracy and Autocracy; Security; peace and fragile states; Sicherheit; Frieden und fragile Staaten; Wirksamkeit und Evaluierung; Effectiveness and evaluation